2012
DOI: 10.1002/bmb.20629
|View full text |Cite
|
Sign up to set email alerts
|

The BOHR effect before Perutz

Abstract: Before the outbreak of World War II, Jeffries Wyman postulated that the Bohr effect in hemoglobin demanded the oxygen linked dissociation of the imidazole of two histidines of the polypeptide. This proposal emerged from a rigorous analysis of the acid–base titration curves of oxy‐ and deoxy‐hemoglobin, at a time when the information on the chemistry and structure of the protein was essentially nil. The magnetochemical properties of hemoglobin led Linus Pauling to hypothesize that the (so called) Bohr histidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…As mentioned earlier, a number of the His p K a ’s were not accessible to NMR in the measurable pH range in both deoxy and oxy HbA. They are α58, α87, α103, α122, β63, and β92.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…As mentioned earlier, a number of the His p K a ’s were not accessible to NMR in the measurable pH range in both deoxy and oxy HbA. They are α58, α87, α103, α122, β63, and β92.…”
Section: Resultsmentioning
confidence: 92%
“…According to Edsall’s review, it was Haldane and collaborators, who in 1914 first proposed that ″one or more acidic groups in the hemoglobin molecule became more strongly acidic when oxygen was bound to the iron″. Another interesting historical account describes the focus of Wyman and co-workers on Histidine (His) residues as the Bohr groups prior to any structural data . Mutation and chemical modification studies also suggested that the titration of histidines, particularly His β146, was involved, , but it was not until X-ray structures were determined by Perutz and his co-workers for unliganded (deoxy) and liganded (oxy; actually met) hemoglobin that an atomic interpretation was suggested.…”
Section: Introductionmentioning
confidence: 99%
“…In retrospect, this confirms intuition (excluding the broader TCR-CD3 complex, of course) on possibilities for a mechanism involving just the five components. Indeed, H-bonding chemistry which effects relatively simple physics is a hallmark of quite diverse protein machinery [28,29]. Also, TCR had k values that varied in either direction-indicating that conformation adjustments might moderate "flush" and "open" pitch without much increasing or decreasing of the dV, viz., R 2 ≈ 0.900 (Suppl.2).…”
Section: Discussionmentioning
confidence: 99%
“…2B). The calculus interprets a comprehensive geometry of the V-domain into a probability of scanning using only the ground-state structure, i.e., without crystallographic data on theoretical conformerssuggesting here, a classic protein function, allostery [28,29]; see also 'protein machinery' in Discussion.…”
Section: This Is Integration Of a 'Volume Element' In Spherical Coordmentioning
confidence: 99%
“…In retrospect, this might confirm intuition (excluding the broader TCR-CD3 complex, of course) on possibilities for a mechanism involving just the five components. Indeed, H-bonding chemistry which effects relatively simple physics is a hallmark of quite diverse protein machinery [24,30]. Also, TCR had k values that varied in either direction-indicating that conformation adjustments might moderate flush and open pitch without much increasing or decreasing of the dV, viz., R 2 ≈ 0.900 (Suppl.1.II).…”
Section: Dq H-bonding Mechanismsmentioning
confidence: 99%